Можливості та наслідки інтродукції видів дуба (Quercus L.) з Великого і Малого Кавказу у дендрарії Національного ботанічного саду ім. М.М. Гришка НАН України - Doroshenko, O.K.; Oleshko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
One of the potential areas of introduction of oak species in Ukraine is Caucasus. With the exception of English oak (Quercus robur L.), which is indigenous to the territory of Ukraine, there is growing 16 species of this genus, 6 of them (Q.castaneifolia C.A.Mey., Q. hartvissiana Stev., Q. iberica Stev., Q. imeretina Stev., Q. longipes Stev., Q. macranthera Fisch. et Mey.) were brought to the Arboretum of M.M. Grуshko National Botanical Garden of the NAS of Ukraine. Based on the literature and our own research, we summed up their introduction. We concluded that short-term observation of introductions, especially in juvenile age, do not give objective data about the success of their introduction. Reliable data can be obtained in the long term observations, which are sometimes measured in decades. Based on this principle, we were able to more objectively, compared to its predecessors, to come to conclusions. We note that from 6 introduced species of oak, only Q. macranthera can be attributed to successfully introduced species.